Bacterial CagA protein compromises tumor suppressor mechanisms in gastric epithelial cells - Palrasu, Manikandan; Zaika, Elena; El-Rifai, Wael; Garcia-Buitrago, Monica; Piazuelo, Maria Blanca; Wilson, Keith T.; Peek, Richard M.; Zaika, Alexander I. (The Journal of clinical investigation, 2020)
Approximately half of the world's population is infected with the stomach pathogen Helicobacter pylori. Infection with H. pylori is the main risk factor for distal gastric cancer. Bacterial virulence factors, such as the oncoprotein CagA, augment cancer risk. Yet despite high infection rates, only a fraction of H. pylori-infected individuals develop gastric cancer. This raises the question of defining the specific host and bacterial factors responsible for gastric tumorigenesis. To investigate the tumorigenic determinants, we analyzed gastric tissues from human subjects and animals infected with H. pylori bacteria harboring different CagA status. For laboratory studies, well-defined H. pylori strain B128 and its cancerogenic derivative strain 7.13, as well as various bacterial isogenic mutants were employed. We found that H. pylori compromises key tumor suppressor mechanisms: the host stress and apoptotic responses. Our studies showed that CagA induces phosphorylation of XIAP E3 ubiquitin ligase, which enhances ubiquitination and proteasomal degradation of the host proapoptotic factor Siva1. This process is mediated by the PI3K/Akt pathway. Inhibition of Siva1 by H. pylori increases survival of human cells with damaged DNA. It occurs in a strain-specific manner and is associated with the ability to induce gastric tumor.